Transmembrane domain length variation in the evolution of major histocompatibility complex class I genes. - Crew, M D (1991)
The fifth exons of major histocompatibility complex (MHC) class I genes encode a transmembrane domain (TM) that is largely responsible for class I antigen cell-surface expression usually through conventional hydrophobic amino acid-membrane interactions or, less often, through phosphatidylinositol linkage. In this report we show that Peromyscus leucopus, a Cricetidae rodent, has MHC class I genes (Pele-A genes) encoding three distinct sizes of TMs. Increases in TM lengths were due to tandem duplications of sequences similar to human hypervariable minisatellite repeats and the lambda chi site. We discerned remnants of a similar duplication event in comparable rodent and primate MHC class I genes. Furthermore, several duplications and deletions appear to have occurred independently in H-2, RT1, Pele-A, and ChLA genes in near-identical positions. Accumulated data suggests that sequences in the fifth exon of MHC class I genes may, therefore, constitute a mutational or recombinational hot spot that is mediated by minisatellite- and chi-like sequences imbedded within the coding region. The MHC class I genes may thus have recruited "selfish" DNA in their evolution to encode cell surface proteins. Expression of Pele-A genes was examined by the polymerase chain reaction (PCR) using oligonucleotide primers specific for exon 4 and 5 sequences. The PCR product sizes indicated that genes encoding each TM domain length are ubiquitously transcribed.